Kesantunan Berbahasa dalam Dialog Stand Up Komedi pada Platform YouTube: Raditya Dika Serial Cerita Cintaku - Muhammad Rizal Almajid; Meidika Dendra Parameswara; Ilhas Lutfie Juliani; Safana Zuhairoh; Asep Purwo Yudi Utomo; Zulfa Fahmy; Amilia Buana Dewi Islamy (Universitas Palan, 2026)
This study analyzes the application of politeness principles in Raditya Dika’s YouTube series Cerita Cintaku using a descriptive qualitative approach within a pragmatic framework. The data consist of 53 utterances collected from four videos, representing Leech’s politeness maxims, including tact, generosity, approbation, modesty, agreement, and sympathy. The findings show that the generosity and modesty maxims are the most dominant, indicating Dika’s consistent effort to maintain ethical and respectful communication by prioritizing audience comfort and feelings. His style reflects empathy, humility, and sensitivity, even when delivering humor in a stand-up storytelling format. These results highlight that entertaining digital content can still uphold politeness values effectively. The study provides useful insights for students, educators, and language researchers in understanding the application of politeness strategies in modern communication contexts. In addition, it offers practical guidance for content creators and public figures to balance engaging content with respectful interaction to build positive and sustainable relationships with audiences in digital platforms today.